The Problem of Catholic School Teachers Deferring to the Home on Controversial Religious Issues - McDonough, Graham P. (Catholic Education: A Journal of Inquiry and Practice, 2010)
This paper observes that an ironic tension occurs in the discussion of controversial issues in some Catholic schools. One technique that teachers use in response to student disagreement with the official Church view on a controversial issue like contraception, homosexuality, or female ordination is to present Church teaching but then suggest that students follow up at home with their parents for further information. While this technique is promising to some degree, it sits uneasily against the remarks that some Catholic education commentators make regarding deficiencies in the home regarding student formation and socialization in the faith. The discussion acknowledges some advantages in this technique, but ultimately concludes that it is flawed because it sidesteps the school’s responsibility to promote higher-order religious thinking and undermines the home-school-Church partnership by placing the responsibilities of families and parishes into schools.